THORACIC SURGERYWhich technique is the best for the surgical management of empyema thoracis in children? - Tander, Burak; Bicakci, Unal; Gunaydin, Mithat; Demirel, Dilek; Rizalar, Riza; Ariturk, Ender; Bernay, Ferit (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction: The differences between single-port (SPT) and two-port techniques (TPT) for the debridement of advanced thoracic empyema in children were evaluated. Material and methods : Age, gender, physical findings, type of thoracoscopic intervention, the length of stay (LOS) and the duration of chest tube drainage (DCTD) were reviewed in 51 patients with thoracic empyema (33 M, 18 F). The SPT was used in 14 patients, while the TPT was used in 37 patients. In the SPT, the telescope itself was used as a dissecting tool. No other instrument was inserted during the debridement. In the TPT, the first port is made for the telescope and the second port for the surgical instrument. A chest tube is inserted through the port site. Results: The empyema was located in the right hemithorax in 24 patients and in the left hemithorax in 25 patients. Two patients suffered from bilateral involvement. The chest tube was removed after a median of 13 days in the SPT and 11 days in the TPT patients. The LOS was a median of 20 days and 13 days in patients from the SPT and TPT groups, respectively. A spontaneously resolved bronchopleural fistula was observed in 4 patients from the SPT group and 2 patients from the TPT group. No significant difference was found between the techniques in terms of age, gender, site of empyema, fever, or the development of bronchopleural fistula. Although the LOS and DCTD were shorter in patients treated with the TPT, the difference was not significant. Conclusions: Although not significant, the TPT for the debridement of advanced empyema in children seems to be more effective in terms of the LOS, DCTD and the risk of bronchopleural fistula.